Patient safety culture as a space of social struggle: understanding infection prevention practice and patient safety culture within hospital isolation settings - a qualitative study - Julian Hunt; John Gammon; Sharon Williams; Sharon Daniel; Sue Rees; Sian Matthewson (BMC, 2022)
Abstract Background In recent times, infection prevention and patient safety have become a global health policy priority with thought being given to understanding organisational culture within healthcare, and of its significance in initiating sustained quality improvement within infection prevention and patient safety. This paper seeks to explore the ways in which engagement of healthcare workers with infection prevention principles and practices, shape and inform patient safety culture within the context of hospital isolation settings; and vice-versa. Research methods In this paper, we utilise focus group interviews at two hospital sites within one health board in order to engage healthcare staff in elaborating on their understandings of infection prevention practices and patient safety culture within isolation settings in their organisation. Focus group transcripts were analysed inductively using thematic analysis in order to identify and develop emerging empirical themes. Results Positioned against a background of healthcare restructuring and ever-increasing uncertainty, our study found two very different hospitals in regard to patient safety culture and infection prevention practice. While one hospital site embodies a mixed picture in regard to patient safety culture, the second hospital is best characterised as being highly fragmented. The utilisation of focus group interviews revealed themes that capture the ways in which interviewees position and understand the work they perform within the broader structural, political and cultural context, and what that means for infection prevention practice and patient safety culture. Conclusion Drawing on the insights of Bourdieu, this paper theorises the field of patient safety as a space of social struggle. Patient safety is thus positioned within its structural, cultural and political context, rather than as merely an epidemiological dilemma.